Both a curse and a blessing? A social cognitive approach to the paradoxical effects of leader narcissism. (November 2022) - Liu, Xin; Zheng, Xiaoming; Li, Ning; Yu, Yu; Harms, Peter D; Yang, Jun
Narcissism is widely considered to be a trait that is commonly found in leaders, but also a characteristic that is frequently a source of problems for their organizations. However, there is accumulating consensus in the organizational literature that, rather than a necessary evil, narcissism can potentially be a mixed blessing for leaders. The present study sets out to reconcile the paradoxical effects of leader narcissism by exploring when and how leader narcissism hampers or helps follower job performance. Utilizing a social cognitive approach to leadership and drawing upon the inferential model of leadership perceptions, we propose that leader effectiveness can shape followers' dual collective leadership perceptions in response to leader narcissism and that these shared perceptions in turn influence follower job performance in opposing manners. The results of multi-wave, multi-source, and multilevel data showed that when leader narcissism was accompanied by low levels of leader effectiveness, followers collectively tended to perceive their leaders as being more narcissistic. However, when leader narcissism was accompanied by high levels of leader effectiveness, followers collectively tended to perceive their leaders as more charismatic. Followers' dual collective leadership perceptions then mediated the joint effects of leader narcissism and leader effectiveness on follower job performance.